Pengembangan Komik Digital Untuk Meningkatkan Literasi Numerasi Siswa Pada Materi Statistika - Niken Lusia Ningrum; Mochamad Abdul Basir; Hevy Risqi Maharani (Jurnal Pendidikan Matematika (JPM), 2023)
This study aims to develop digital comic media to improve students' numeracy literacy in statistical material. Digital comic is mathematics learning comics for statistics material with the aim of increase students' numeracy literacy. This type of research was in the form of development used the ADDIE method (analyzed, designed, developed, implemented, and evaluated). In the research, validation was carried out (material experts, media experts, and mathematics teachers) and practicality analysis, The techniques used to collect research data included validation sheet questionnaires, student and teacher response questionnaires. In this study, based on the collection of data and information in the digital comic media field, it met the valid, and practical,.Digital Comic Media got a validity value of 89.7% (very valid), got a practicality level response from the teacher of 88.3% (very practical), from students of 86.4% (very practical).